Statistical methods for source apportionment - Krall, Jenna R.; Chang, Howard H. (Handbook of Environmental and Ecological Statistics, 2019)
Exposure assessment covers the entire process of estimating exposures, including the design of the exposure data collection, exposure measurement, and exposure modeling. The purposes of environmental exposure assessment fall into three broad classes: environmental surveillance, quantification of population exposure distributions for risk assessment, and inference about health effects in environmental epidemiology studies. Ecologic time series studies relate time-varying (e.g. daily average) estimates of exposure to time-varying numbers of events. These are common in the field of air pollution epidemiology to relate day-to-day variation in pollutants to day-to-day variation in total mortality counts. The case-crossover design is an observational study analogue to the classic crossover study, an experimental design where subjects receive both intervention and control conditions in order to ascertain the average within-subject effect of the intervention. In the case-crossover study, outcomes occur at known times and in settings where exposure is believed to acutely affect the outcome.